2022
DOI: 10.3390/foods11152261
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Bioactive Ingredients in Sesame Oil Affected by Multiple Roasting Methods

Abstract: Roasting is an important step in sesame (Sesamum indicum L.) processing. The current research was undertaken to evaluate the oil content, fatty acid (FA) profiles, andphysicochemical characteristics of oil recovered from sesame roasted by different methods (cooker oven, stovetop pan, microwave, and electric frying pan). Roasting sesame seeds changed their oil content according to the roasting method used, with content ranging from 49.83% in control to 59.85% in the roasting by microwave. In oils recovered from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 81 publications
2
7
0
Order By: Relevance
“…Özdemir et al (2018) reported that β‐sitosterol (63.73%) was the most abundant sterol in sesame seeds, followed by campesterol (20.15%), Δ5‐avenasterol (8.58%), stigmasterol (5.28%), and Δ7‐stigmasterol (2.26%). El‐Beltagi et al (2022) identified ergosterol, cholesterol, stigmasterol, and β‐sitosterol as the main sterols in sesame oil, with stigmasterol and β‐sitosterol being the most abundant phytosterols in the profiles, consistent with the findings of this study.…”
Section: Resultssupporting
confidence: 91%
“…Özdemir et al (2018) reported that β‐sitosterol (63.73%) was the most abundant sterol in sesame seeds, followed by campesterol (20.15%), Δ5‐avenasterol (8.58%), stigmasterol (5.28%), and Δ7‐stigmasterol (2.26%). El‐Beltagi et al (2022) identified ergosterol, cholesterol, stigmasterol, and β‐sitosterol as the main sterols in sesame oil, with stigmasterol and β‐sitosterol being the most abundant phytosterols in the profiles, consistent with the findings of this study.…”
Section: Resultssupporting
confidence: 91%
“…According to Table 1 , the chemical parameters of IPPO, including acid, peroxide, iodine, and saponification values, differed greatly depending on the region. The acid values of IPPO ranged from 0.98 ± 0.02 to 2.25 ± 0.02 mg KOH/g, which was lower than that of sesame oil (3.78 mg KOH/g) [ 29 ] and walnut oil (2.49 mg KOH/g) [ 30 ]. The low acid value indicated that IPPO had strong storage stability, low oil rancidity, and good quality, making it suitable as an edible oil.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, 500 µL of headspace samples was automatically injected into the injector (85 °C, splitless mode) by means of a heated syringe. Nitrogen of 99.999% purity was used as the carrier/drift gas at programmed flow rates as follows: EPC1 (IMS drift gas) was maintained at 150 mL·min −1 , EPC2 (GC carrier gas) was initially maintained at 2 mL·min −1 for 2 min and then increased to 100 mL·min −1 within 18 min [ 39 , 40 ]. N-ketones C 4 -C 9 (Sinopharm Chemical Reagent Co., Ltd., Beijing, China) were used as external references to calculate the retention index (RI) of volatile compounds.…”
Section: Methodsmentioning
confidence: 99%